2017
DOI: 10.1039/c7ra10435a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oxidized tyrosine products on insulin secretion via the thyroid hormone T3-regulated TRβ1–Akt–mTOR pathway in the pancreas

Abstract: Oxidized tyrosine products (OTPs) have been detected in commercial foods with high protein content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Dityrosine was found to be responsible for the suppression of the T3 function in upregulating insulin synthesis‐related genes ( Ins2 , MafA , Pdx1 ). A further study (Ding, Tang et al., ) corroborated the lack of sensitivity of pancreatic islets to T3 after 12 weeks of dietary administration of oxidized tyrosine and dityrosine (8 g/kg diet). The authors proposed that both dityrosine and T3 may compete for the binding domain of TR β 1 receptors in pancreatic cells, disturbing the T3‐activated translation factors involved in the Akt–mTOR signaling pathway.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 77%
“…Dityrosine was found to be responsible for the suppression of the T3 function in upregulating insulin synthesis‐related genes ( Ins2 , MafA , Pdx1 ). A further study (Ding, Tang et al., ) corroborated the lack of sensitivity of pancreatic islets to T3 after 12 weeks of dietary administration of oxidized tyrosine and dityrosine (8 g/kg diet). The authors proposed that both dityrosine and T3 may compete for the binding domain of TR β 1 receptors in pancreatic cells, disturbing the T3‐activated translation factors involved in the Akt–mTOR signaling pathway.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 77%
“…After ingestion, they can be absorbed into the blood circulation through the intestine and accumulate in the liver, kidney, pancreas, and brain . A study found that long-term feeding of OTP in mice can trigger pancreatic oxidative stress and induce liver and kidney fibrosis, and learning and memory dysfunction . Metabolomics analysis showed that the administration of 320 μg/kg DT solution for 6 weeks significantly reduced plasma 3-hydroxybutyrate and albumin levels, increased the content of trimethylamine oxide in plasma and urine, inhibited fatty acid metabolism and protein synthesis, and increased the risk of cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…After T3 enters into cardiomyocytes, it binds to the thyroid hormone receptor and retinoic acid X receptor (RXRα) and coactivators, such as steroid receptor coactivator (Src-1), to regulate the expression of multiple target genes . Ding et al found that Dityr has a structure similar to T3, which can competitively bind to the pancreatic T3 receptor and inhibit the physiological effects of T3, resulting in insufficient ATP production and decreased insulin secretion in pancreatic cells . BPA and PCBs as structural analogs of T3 cause endocrine disorders and disrupt T3 action during development .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of di-Tyr in foods, and consequent dietary intake, has resulted in studies on its toxicological properties. Intragastric administration of pure di-Tyr has been associated with metabolic alterations [ 151 ], including disrupted glucose metabolism [ 152 ], and renal alterations [ 153 ]. Interestingly, and of potential biological relevance, processed milks containing di-Tyr (and other Tyr oxidation products) can induce oxidative damage in plasma, liver and brain tissues, as well as spatial learning and memory impairments [ 154 ].…”
Section: Types Of Crosslinks Detected Within and Between Proteins And Peptidesmentioning
confidence: 99%